2009
DOI: 10.1111/j.1346-8138.2008.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐localization of inducible nitric oxide synthase and phosphorylated Akt in the lesional skins of patients with melasma

Abstract: Activation of the inducible nitric oxide synthase (iNOS)/nitric oxide (NO) pathway in keratinocytes has been reported to be associated with the pathogenesis of melanogenesis. Akt activation plays an important role in the activation of the transcription factor nuclear factor (NF)-kappaB and subsequent elevation of iNOS expression. In the present study, we highly detected both iNOS protein and Akt phosphorylation in keratinocytes of the basal layer of the epidermis at the junction with the dermis of melasma skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 27 publications
0
40
0
1
Order By: Relevance
“…Tomita et al reported that ultraviolet-B radiation induced prostaglandin secretion and that prostaglandins E 2, thromboxane B 2 , and leukotriene C 4 , particularly, result in larger and more dendritic melanocytes. 37,38 The release of cytokines and prostaglandins following sun exposure could have stimulatory effects on melanocytes in patients with melasma, and thus explain dermal hyperpigmentation and inflammation as it occurs in postinflammatory hyperpigmentation. 37,39 When activated, human dermal fibroblasts secrete several melanogenic cytokines, such as stem cell factor and hepatocyte growth factor, which increased in melasma skin, suggesting that the increase in fibroblast number and activation leads to changes in the fundamental substance, dermal elastosis, and melanocyte activation in ultraviolet-radiated skin.…”
Section: Discussionmentioning
confidence: 99%
“…Tomita et al reported that ultraviolet-B radiation induced prostaglandin secretion and that prostaglandins E 2, thromboxane B 2 , and leukotriene C 4 , particularly, result in larger and more dendritic melanocytes. 37,38 The release of cytokines and prostaglandins following sun exposure could have stimulatory effects on melanocytes in patients with melasma, and thus explain dermal hyperpigmentation and inflammation as it occurs in postinflammatory hyperpigmentation. 37,39 When activated, human dermal fibroblasts secrete several melanogenic cytokines, such as stem cell factor and hepatocyte growth factor, which increased in melasma skin, suggesting that the increase in fibroblast number and activation leads to changes in the fundamental substance, dermal elastosis, and melanocyte activation in ultraviolet-radiated skin.…”
Section: Discussionmentioning
confidence: 99%
“…Other hypotheses on melasma pathogenesis include a) an upregulation of genes modulating Wnt and prostaglandin pathways [68]; b) the involvement of non-coding RNA (H19 gene) [69]; c) the UVmediated increase in inducible nitric oxide synthase (iNOS) levels, which can activate the AKT-NFkB pathway [70,71]. Finally, a genetic predisposition has been suggested in melasma development by reports of family occurrence [72].…”
Section: Melasma Pathogenesismentioning
confidence: 99%
“…The elevated expression of vascular endothelial growth factor (VEGF) in keratinocytes has led to the hypothesis that VEGF may play a role in the behavior of the melanocytes in the skin, because functioning VEGF receptors were demonstrated in melanocytes in vitro [26]. Elevations in the levels of c-kit, SCF, and inducible nitric oxide synthase have also been observed, which could affect vascularization [27,28].…”
Section: Increased Vascularizationmentioning
confidence: 99%